Центральні важелі розвитку периферичної інсулінорезистентності - Кіхтяк, О. П.; Орел, Ю. Г.; Скрипник, Н. В.; Москва, Х. А. (Clinical Endocrinology and Endocrine Surgery, 2012)
Control of energy consumption and expenditure is to be referred as lipostatic theory. Its core feedback signals include insulin and leptin. Their complex interaction with central receptors determine an eating humane behavior. Several medicines, acting toward certain receptors in a brain alleviate insulin resistance (pyoglitazone) and leptin resistance (metformin) in patients with type 2 diabetes mellitus providing normal work of lipostasis.